The Optimal Capacity of the Handling Facilities in Bitung Container Terminal (Naval Architecture Departement, Hasanuddin University, 2022)
The Bitung container terminal as the international hub port experienced an increase in the growth of container flow and ship call from 2014 to 2019, wherein the average increase was 8% and 4%, respectively. In 2018, the increase of ship calls was significantly high about 25% compared with the ship call in 2017. One of the important port facilities, to support the loading and unloading activities for the container, is the container handling types of equipment that are used for container handling from ship to port, port to the container terminal, and in the container terminal itself. The aims of this study are to analyze the productivity performance of the container handling equipment in the Bitung container terminal by considering the growth of container flow and to determine the optimal capacity of the container handling capacity for the expected year in 2035. The container handling equipment that was investigated is a container crane (CC), rubber-tired gantry (RTG), and head track (HT). The combination of the qualitative and quantitative methods is used for analyzing the productivity, and the regression method is used for predicting the growth of the container. Also, the optimization method is used for determining the optimal capacity of the container handling equipment. The research results revealed the productivity of CC, RTG, and HT were 25 boxes/hour, 27 TEUS/hour, and 24 TEUS/hour, respectively. In addition, the optimal capacity of CC is one unit for the short term (2025) and mid-term (2035). The optimal capacity of RTG is two units for the short-term (2025) and mid-term (2035). For the HT, the optimal capacity is two units for the short-term (2025) and mid-term (2035).